The Concept Of Pluralism In Islamic Education - Anas M. Adam (Ar-Raniry: International Journal of Islamic Studies, 2017)
Religious pluralisme is a term used to refer to positive attitudes toward world religions (e.g., Islam, Christianity, Hinduism, Budhism, Catholic, etc) with the aim ofcreating a harmonious, peaceful, and prosperous life within a pluralist society byupholding people's equal rights to live peacefully in this world. The aim of this articleis to elaborate on the concept of religious pluralism and its relation to Islamic education. There have been a controversy caused by the differing definitions ofreligious pluralism, which has led to certain misconceptions and hence its alienation from Islamic education in general. In the face of such challenges, efforts mustcontinually be made to foster mutual understanding and respect between people ofdifferent religions in order to avoid potential conflicts, either between peopleembracing different religions or people within the same religion. It is this positiveawareness which religious pluralism seeks to foster. Thus, incorporating the conceptof pluralism into Islamic education is a must, especially by making change to thesystem of Islamic education which for a long time has focused only on buildingindividual or communal piety. The new priority should be given to the creation ofsocial sensitivity toward pluralism, either through cultural, language, or religiousinterventions. This all aims at reinforcing the notion of Islam as Rahmatallil’alamin.